2015
DOI: 10.1002/adv.21509
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Processing, Characterization and Erosion Wear Response of Linz–Donawitz Slag Filled Epoxy Composites

Abstract: This paper reports a study on erosion response of epoxy composites filled with micro‐sized Linz–Donawitz (LD) slag particles. LD slag is a major solid waste generated in huge quantities during steel making. It comes from slag formers such as burned lime/dolomite and from oxidizing of silica, iron etc. while refining the iron into steel in the LD furnace. Although a number of ways for its utilization have been suggested in the past, its potential as a filler material in polymeric matrices has not yet been explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Figure shows the effect of fiber content on the void content of composites. Generally, the measured density is always less than the theoretical density, which excludes all the pores due to buoyancy effect caused by the trapped air . It is observed from the figure that the void percentage increases with the increase in fiber content.…”
Section: Resultsmentioning
confidence: 97%
“…Figure shows the effect of fiber content on the void content of composites. Generally, the measured density is always less than the theoretical density, which excludes all the pores due to buoyancy effect caused by the trapped air . It is observed from the figure that the void percentage increases with the increase in fiber content.…”
Section: Resultsmentioning
confidence: 97%
“…[16] The actual density (ρ ce ) of the composite is determined experimentally by simple water immersion technique. [16] The actual density (ρ ce ) of the composite is determined experimentally by simple water immersion technique.…”
Section: Physical and Mechanical Studiesmentioning
confidence: 99%
“…The theoretical density (ρ ct ) of all prepared composite materials on the basis of weight fraction is estimated by the relation given by Pati and Satapathy. [16]…”
Section: Physical and Mechanical Studiesmentioning
confidence: 99%
“…It is shown that the coating is suitable for the relative mild conditions of liquid–particle two‐phase flow. It has been reported by Pati et al , Biswas et al and Srivastava et al that compared with the fiber‐reinforced composite, the particle filler has a significant effect on the erosive performance of the hybrid composite. The incorporation of particle fillers results in the improvement of erosive resistance of fiber‐reinforced polymer composites.…”
Section: Introductionmentioning
confidence: 96%